2008
DOI: 10.1007/s12288-008-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant induced artefacts in peripheral blood smears

Abstract: Microscopic evaluation of a peripheral blood smear is one of the most benefi cial test. But anticoagulant induced artefacts could lead to misinterpretation of the smears. The present study was undertaken to identify the anticoagulant induced artefacts and avoid misinterpretation of peripheral blood smears. The blood samples were collected using Ethylene Diaminetetraacetic acid (EDTA) and Sodium citrate, mixed thoroughly and smears were made immediately as well as 1hr apart for 6 hrs, stained and examined under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…These artefacts are likely to be caused by a lysolecithin formation or fall in Adenosine Triphosphate (ATP) as the blood is kept for a long time. 4 So the current study was undertaken to identify storage related morphological changes in blood cells so that these artefactual changes are not misinterpreted as pathologic findings.…”
Section: Introductionmentioning
confidence: 99%
“…These artefacts are likely to be caused by a lysolecithin formation or fall in Adenosine Triphosphate (ATP) as the blood is kept for a long time. 4 So the current study was undertaken to identify storage related morphological changes in blood cells so that these artefactual changes are not misinterpreted as pathologic findings.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, our observance is identical to study Brent L. wood et al 7 Causes for reduced WBC count can be cytoplasmic changes such as degranulation, vacuolization, degeneration, sometimes blebs formation & karyolitic changes & lobulations in their nucleus. 14 In relation with prior studies, it is stated that the statistically significant decrease in platelet count at all temperature begins after 6 hrs of sample collection. 2,15 While, in this present study, we have observed that platelet count also has reduced in stored blood samples at room temperature because of aggregation & swelling of platelets.…”
Section: Discussionmentioning
confidence: 75%
“…This observance is similar to other prior studies. 14 Hence, in order to get standard haematological results it is necessary to maintain blood samples at fixed 4 • C in conditions of extended period of evaluation, because previous studies proved that blood storage at 2 • C may lead to freezing injury to RBCs results in hemolysis. However, storage at > 6 • C lead to overgrowth of unspecified bacteria during sampling of blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on peripheral blood smear cited morphological changes began beyond 2hrs and are prominent after 6 hours. 9 We observed pronounced degenerative changes in smear of room temperature stored samples, which may be misinterpreted as pathological findings and thus leading to incorrect diagnosis. However by storing the blood samples at 4 0 C we could maintain the cell morphology.…”
Section: Discussionmentioning
confidence: 78%